Analisis Yuridis atas Tidak Dilaksanakannya Putusan Pidana yang Telah Berkekuatan Hukum Tetap dalam Perspektif Kepastian Hukum - Adib Adib; Sanusi Sanusi; Gunadi Rasta (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the factors causing the non-implementation of criminal decisions that have permanent legal force and examine the legal consequences that arise from the perspective of legal certainty. The research method used is normative juridical. The results of the study indicate that the non-implementation of criminal decisions that have permanent legal force is caused by the defendant not being in the detention process, so that after the decision has permanent legal force, the defendant goes into hiding or runs away; the defendant during the trial process until after the verdict is read out his status is still under city or house arrest; and the defendant runs away during the trial stage. The legal consequence of the non-implementation of criminal decisions that have legal force is that the state risks losing the authority to carry out criminal penalties due to the passing of the expiration of the grace period.